Estimasi Biomassa dan Karbon Serasah di Kawasan Aliran Mata Air Panas Jaboi, Kecamatan Sukajaya, Kota Sabang - Raihan Raihan; Muslich Hidayat; Nurdin Amin; Zuraidah Zuraidah; Lina Rahmawati (Lembaga Pengembangan Kinerja Dosen, 2025)
Tropical forests play an important role as carbon sinks and biomass stores, including through the litter produced by vegetation. Litter contributes to nutrient cycling, maintains soil fertility, and is an important component of ecosystem carbon reserves. This study aims to estimate the biomass and carbon content of litter in the Jaboi Hot Spring Flow Area, Sukajaya District, Sabang City. The study was conducted in June 2025 using a 100 m long line transect method with four transects, each consisting of 18 1 x 1 m plots. Leaf litter samples were collected, their wet weight was measured, dried in an oven for 48 hours, and their carbon content was calculated based on the percentage of organic carbon of 0.47. The results showed a total litter biomass of 8,106 kg/m² with an average of 2,027 kg/m², and a total litter carbon of 3,809 kg/m² with an average of 0,952 kg/m². The highest values were found at Station 3 (2,354 kg/m² and 1,106 kg/m²) and the lowest at Station 1 (1,691 kg/m² and 0,795 kg/m²). Variations in values are influenced by soil physical-chemical factors, vegetation density, and climatic conditions, which influence production and decomposition rates. These results emphasize the importance of monitoring biomass and litter carbon to support forest management and conservation.